Dissolved Microbial Methane in the Deep Crystalline Crust Fluids–Current Knowledge and Future Prospects - Femke van Dam; Riikka Kietäväinen; Henrik Drake (Geofluids)
Methane is a powerful greenhouse gas, of which most is produced by microorganisms in a process called methanogenesis. One environment where methanogenic microorganisms occur is the deep biosphere. The deep biosphere environment comprises a variety of ecosystem settings; marine habitats such as subseafloor sediments, rock pore volumes within subseafloor basalts, and terrestrial settings such as sedimentary rocks and crystalline bedrock fracture networks. Microbial methane formed in these environments influence the biological, chemical, and geological cycles of the upper crust, and may seep out of the deep into the atmosphere. This review focuses on the process of microbial methanogenesis and methane oxidation in the relatively underexplored deep crystalline-bedrock hosted subsurface, as several works in recent years have shown that microbial production and consumption occur in this energy-poor rock-fracture-hosted environment. These recent findings are summarized along with techniques to study the source and origins of methane in the terrestrial crust. Future prospects for exploration of these processes are proposed to combine geochemical and microbial techniques to determine whether microbial methanogenesis is a ubiquitous phenomenon in the crystalline crust across space and time. This will aid in determining whether microbial methane in the globally vast deep rock-hosted biosphere environment is a significant contributor to the global methane reservoir.